TOWARDS THE BEGINNING OF AN APPLICATION OF THE NEW MISDEMEANOR LAW - Martinović, Aleksandar (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
Administrative law and Misdemeanor law are two different branches of the legal system. Administrative law is one of the fundamental disciplines if public law, while the Misdemeanor law is much closer to the criminal law and the law of economic offenses, so in the board sense it is a form of criminal law. According to established academic tradition, administrative and legal theorists also deal with basic misdemeanors terms, mainly because they were considered as so-called police offenses in the past. Law on Misdemeanor adopted in 2013 establishes the infringement procedure as a standard court procedure, whereby the administrative bodies completely stopped to be competent for their conduct and the imposition of sanctions. Therefore, studying of Misdemeanor law under Administrative law is going to have only academic and pedagogical justification after the new law begins to apply.